2017
DOI: 10.12788/jhm.2747
|View full text |Cite
|
Sign up to set email alerts
|

Rates, Predictors and Variability of Interhospital Transfers: A National Evaluation

Abstract: In this nationally representative evaluation, we found that a sizable number of patients undergo IHT. We identified both expected and unexpected patient and hospital-level predictors of IHT, as well as unexplained variability in hospital transfer rates, suggesting lack of standardization of this complex care transition. Our study highlights further investigative avenues to help guide best practices in IHT. Journal of Hospital Medicine 2017;12:435-442.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(93 citation statements)
references
References 28 publications
3
90
0
Order By: Relevance
“…First, given the criteria we used to define transfer, it is possible that we included nontransferred patients within our transferred cohort if they were discharged from one hospital and admitted to a different hospital within 1 day, although quality assurance analyses we conducted in prior studies on these data support the validity of the criteria used. 2 Second, we cannot exclude the possibility that patients received nonprocedural specialty care (ie, expert opinion, specialized imaging, medical management, management of secondary diagnoses, etc.) not available at the transferring hospital, although, arguably, in select patients, such input could be obtained without physical transfer of the patient (ie, tele-consult).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, given the criteria we used to define transfer, it is possible that we included nontransferred patients within our transferred cohort if they were discharged from one hospital and admitted to a different hospital within 1 day, although quality assurance analyses we conducted in prior studies on these data support the validity of the criteria used. 2 Second, we cannot exclude the possibility that patients received nonprocedural specialty care (ie, expert opinion, specialized imaging, medical management, management of secondary diagnoses, etc.) not available at the transferring hospital, although, arguably, in select patients, such input could be obtained without physical transfer of the patient (ie, tele-consult).…”
Section: Discussionmentioning
confidence: 99%
“…© 2018 Society of Hospital Medicine we used in our prior research. 2 Beneficiaries transferred to the same hospital, those with greater than 1 transfer within the same hospitalization, or those cared for at hospitals with "outlier" transfer-in rates equal to 100% or transfer-out rates greater than 35% were excluded from analysis given the suggestion of nonstandard claims practices.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is subject to several limitations. This is a single site study; given known variation in transfer practices between hospitals, 3 it is possible that our findings are not generalizable. However, given similar existing data on patients admitted through the ER, it is likely our findings may be reflective of IHT to similar tertiary referral hospitals.…”
Section: Discussionmentioning
confidence: 94%
“…A study using the American College of Surgeons National Surgery Quality Improvement Program found that interhospital transfer is an independent risk factor for mortality, morbidity, and high resource utilization [9] . These worse outcomes could be due to delay in diagnosis and initiation of transfer, availability of bed space in the receiving hospital, medical errors from transition of care, and the complex logistics of IHT [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%